Schooling of Young people and adults in areas of agrarian reform of the State of Parana: the experience of UNIOESTE - Adrian Alvarez Estrada; Valdecir Soligo (Universidade Federal do Norte do Tocantins, 2021)
The aim of this essay is to present the dynamics and results achieved through the youth and adults schooling project - final years of elementary school (phase II) -in areas of agrarian reform of the State of Parana. We sought to describe the essence of the project in order to highlight the importance of educational actions focused on attending to latent social demands in the history of Brazilian education. As a methodology, we used documentary analysis, based on the scope of the project and the relevant legislations, with the specialized bibliography to reach the presentation of the results obtained with the development of the course. As a result, we have the remarkable presence of the difficulties of the EJA modality, in addition to the reality of rural communities, mainly linked to social movements, but in the contradictory process, the demand for education is highlighted in the number of enrollments and evidenced in the relationship of seniors, revealing a reality still present in our country.